EDUKASI HUKUM BAGI PELAKU BULLYING DAN HATESPEECH DIKALANGAN REMAJA: Legal Education for Bullying and Hatespeech Persons among Youth - Zuhdi Arman; Yenny Fitri Z; Anna Andriany Siagian (ASOSIASI IDEBAHASA KEPRI, 2023)
Both positive and negative effects arise as a result of social media's widespread use and its ever-increasing rate of development. The positive effect is that it becomes simpler for data to circle among people in general, structure assessments, online business, etc. Moreover the adverse consequences, for example, criticize, dangers, slander, the development of negative sentiments and what is famous today is disdain discourse and digital tormenting. The prevention of bullying and hate speech for SMAN 2 Bukittinggi students, particularly those in grade 10, will be examined in this paper. This action expects to help members to bring issues to light since the beginning about the need to try not to menace in day to day existence. Partners will learn about the dangers and effects of bullying themselves through this service project. The execution of this action got a positive reaction from accomplices where the action members from accomplices were happy with the data and schooling conveyed. In addition, the implementation activities of both the socialization and education that were carried out were games and brief quizzes about preventing bullying and hate speech. At SMAN 2 Bukittinggi, this activity was carried out offline. The objective of these games and quizzes is to gain an in-depth understanding of each partner's awareness of the dangers posed by bullying and hate speech.